Effects on Self-Esteem, Interpersonal Relations Ability and Job Stress In Apartment House Private Security Guards - Kim, Ja-Ok; Park, A Young; Kim, Hyun-Suk; Park, Hae-Ryoung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to provide basic data for policy development to improve health promotion and self-esteem of apartment house private security guards. This study is to investigate the degree of job stress, interpersonal ability and self-esteem of apartment house private security guards.Methods/Statistical analysis: The subjects were 97 apartment house private security guards at G city. The research method was used by citing 24 short items of Korean job stress measurement tool, and the interpersonal relationship ability tool was used by Performance Solution International (PSI). A four-point scale with 10 items was used to measure self-esteem. The analysis of differences in job stress, interpersonal relationship ability and self-esteem was analyzed by independent t-test and one-way ANOVA. The correlation between job stress, interpersonal relationship ability and self-esteem was analyzed by Pearson's correlation.Findings: Age of the subjects, 60 people were younger than 70 years of age (61.9%), and 42 people were 70 or older (38.1%), and the mean age was 68.2±4.9. There was a statistically significant difference in the job stress of the subjects between age (t = 2.0 p = .049), presence of restructuring (t = 2.83, p = .006), presence of exercise (t = -2.52, p = .013) there was. There was a statistically significant difference in the ability of interpersonal relationship ability among the subjects with and without smoking (t = -2.03, p = .045). The self- esteem of the subjects was statistically significant at the level of education (F = 3.27, p = .042). The subjects' job stress and interpersonal relationship ability (r = -. 206, p = .043) showed a negative correlation. Interpersonal relationship ability and self-esteem (r = .554, p